How Can The Implementation of Enterprise Resource Planning (ERP) Systems Contribute to the Long Term Sustained Growth and Development and Streamlining of Business Processes in the Wind Power Generation Sector? - Sharma, Maneesh (2009)
The research aims to study and present an overview of the contribution of Enterprise Resource Planning (ERP) Systems to the long term sustained growth, development and streamlining of business processes in the wind power sector. The research topic is briefly introduced and a basic understanding of research question is developed to provide initial comprehension of the topic. The research progresses in a phased style and is composed of chapters giving an individual helicopter view of the topic introduced and discussed.